NEGOSIASI IDENTITAS PADA ANAK BERKEBUTUHAN KHUSUS - Marida Sariningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to determine the identity formation process in children with cleft lip in Curup Village Merigi Sakti District Central Bengkulu Regency. The research method was descriptive qualitative method. Informants in this study were 16 people,consists of 3 children with cleft lips, three parents, four neighbors of the children with cleft lips and 3 children who play with them.Data were collected by observation, library research, interview and documentation.The results showed that: (1) children with cleft lips disabilities communication was limited due to interference with their speech;(2) children with with cleft lips disabilitiesobtained theircomfort identities to some people who live with them, but feel uncomfortable with people who mocked their disability; (3) the comfortidentity gained by children with cleft disabilities with people they know; 4) the family ties were considered by children with cleftdisabilities as a bond that support their identity; (5) The support of parents was done through various activities such as buying clothes and take them for a walk;( 6) the identity stabilityof children with cleftlips as members of societycould happen when parents were able to understand their needs, but the identity was unsteady when there were those who mocking at them;(7) the provision of affection or special attention weretake them for a walk and buy new clothes that formed the satisfaction as the results of negotiations identity;(8) communications made by children with cleft lips with people around them couldn’t run effectively as they need to speak repeatedly to make their communicants understand.